The Changed and Unchanged Situation in The Representation of Women in Contemporary Cinema - Arif Rohman (UPP FIB UGM (No.02;Juni 2013;Vol.25), 2013)
The Changed and Unchanged Situation in The Representation of Women in Contemporary Cinema: feminis,hermeuneutics,jender,layar lebar,perempuan